Inferior vena cava agenesis-associated thrombosis in a neonate - Javed Ahmed; Hari Balasubramanian; Vaseem Ansari; Nandkishor Kabra (Wolters Kluwer Medknow Publications, 2021)
Background: Inferior vena cava (IVC) malformations are rare developmental anomalies and are usually asymptomatic. Agenesis of IVC is an uncommon form of IVC malformation, and symptomatic neonatal presentation is unusual. We describe an unusual case of symptomatic venous thrombosis in the neonatal period after central venous cannulation, which was later found to have agenesis of IVC. Clinical Description: An extreme preterm (28 weeks) baby developed deep vein thrombosis of the femoral and external iliac vein after femoral venous catheterization and required anticoagulation therapy. Later, during the hospital stay, he was noted to have developed dilated abdominal veins over the flanks and paraspinal region, with the direction of flow below upward 2 months after the resolution of the thrombus. Management and Outcome: Ultrasonography (USG) color Doppler ruled out portal hypertension or persistence of IVC obstruction. Computed tomography (CT) venography resolved it to be the case of agenesis of the infrarenal portion of IVC. No consensus guidelines exist for neonatal management and it is usually conservative. Conclusion: IVC developmental anomalies including agenesis of IVC are very rare and are usually an asymptomatic condition, but can cause symptoms due to venous congestion in the lower limb or pressure from enlarged collaterals and rarely associated with deep venous thrombosis usually seen in young adults. Neonatal presentation is extremely rare. Diagnosis is by USG color Doppler and CT venography. Neonatal management guidelines are lacking and the risk of anticoagulation must be cautiously weighed against the risk of hemorrhage.